Het groetend kindje - De Boeck, August; Lambrechts, Lambrecht (Antwerpen : Muziekdrukkerij Jan Boucherij.)
Bibliotheek Camille Huysmans
Partituur met tekst
Nederlands
Partituur
Keywords: partituren; liederen